Analisis Model Verhults kaitannya dengan Ketersediaan Dokter Umum di Kabupaten Timor Tengah Selatan (TTS) - Ariyanto Ariyanto (J-Icon : Jurnal Komputer dan Informatika, 2019)
TTS Regency is the second largest regency with the highest population in East Nusa Tenggara. The ratio of general practitioners from 2015 to 2017 is below national standard. Therefore, the TTS regency has experienced a crisis of general practitioners. The research was conducted by taking the number of TTS population of the last eight years. We use the Verhulst model to predict the number of population and propose the ideal number of general practitioners. We found that the number of TTS population is predicted to be 647.815 in 2027. Furthermore, the ideal number of general practitioners in 2027 is 259 people.